Consumer knowledge, attitude, and perception toward the use of Monosodium Glutamate (MSG) in the Philippines - Miguel, Jozelle Mae B. (College of Home Economics, University of the Philippines Diliman, 2023)
The use of monosodium glutamate (MSG) remains a contentious topic among consumers due to perceived health risks, despite limited scientific evidence, particularly in the Philippines where its widespread use contrasts with the lack of research on consumers' knowledge, attitude, and perception (KAP) regarding its use. Thus, the study administered a structured questionnaire to evaluate the KAP of adult Filipino consumers (n = 444) across Luzon, Visayas, and Mindanao, regarding the use of MSG. Data analysis revealed that the majority of consumers obtained scores ranging from 5 to 7 out of 10, indicating an average level of knowledge regarding MSG, with younger and more educated respondents having higher knowledge scores. Respondents from Luzon and Mindanao had significantly higher (p<0.05) knowledge scores compared to those from Visayas. Consumers with neutral level of concern about MSG had lower knowledge scores compared to those who were not concerned. Regarding attitude, consumers generally agreed slightly with statements highlighting MSG's benefits and remained neutral towards its health effects based on the 5-point Likert Scale. Factor analysis revealed that attitudes towards MSG were influenced by risk and benefit perceptions, with more knowledgeable and less concerned consumers perceiving greater benefits and lower risks. These findings underscore the need for extensive education and accurate information about MSG to address misconceptions and concerns among consumers and subsequently facilitate its use in food preparation and maximize its associated benefits. Lastly, further research on consumers' KAP of seasoning products and other food items containing MSG may be considered.